The Gambia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
This Selected Issues paper and Statistical Appendix for The Gambia underlies that the exchange rate is broadly in line with fundamentals, although data weaknesses and uncertainties prevent a definitive assessment. The Gambia's current account deficit is higher than economic fundamentals would predict, and a depreciation of 11 percent would be needed to restore sustainability. The external sustainability approach suggests that 4-6 percent depreciation is needed for the current account deficit to be consistent with constant net foreign assets as a share of GDP.